Analisis Pendekatan Ekspresif pada Novel “Cantik Itu Luka” Karya Eka Kurniawan - Elvina Fransiska Hutabarat; Junifer Siregar; Martua Reynhat Sitanggang Gusar (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2021)
This study aims to describe the expressive approach to the novel "Cantik Itu Luka" by Eka Kurniawan. The analysis in this study is the novel "Cantik Itu Luka" by Eka Kurniawan. The formulation of the problem discussed in this study is how the novel "Beautiful Is a Wound" is analyzed with an expressive approach. This study used qualitative descriptive methods to collect data conducted using the recording technique method. Based on the data collection method used, the data will be analyzed by reading the novel, understanding the content of the novel carefully, looking for imagination, emotions, expressing the author's ideas and psychology, and then collecting them into one data according to their classification. . The data in this study is in the form of text in the novel that shows the author's expressiveness. The results of this study found the form of the author's expression in the novel "Cantik Itu Luka" by Eka Kurniawan, namely how the author can show his expression.